Mean annual increment of Dysoxylum parasiticum (Osbeck) Kosterm. in â€œEka Karyaâ€ Botanical Garden, Bali - NI KADEK EROSI UNDAHARTA; BRAMANTYO TRI ADI NUGROHO; MUSTAID SIREGAR (Biodiversitas Journal of Biological Diversity, 2008)
Dysoxylum parasiticum (Osbeck) Kosterm. including into the tribe of Meliace. The society in Bali calls this plant with majegau. It gives a special characteristic for Balinese and has advantages in their religion. In Bali, it is more known as divine tree (kayu dewa), which able to be used for purified building. The objective of this research was to measure the mean annual increment of height, diameter and volume of D. parasiticum. Recognizing the characteristic of this plant is an important step to get information about the growth of majegau. Estimation of age harvest and also the conservation effort as one of effort to take care of its continuity. The results showed that highest heightincrement in XIVA garden bed, and the highest diameter increment in XVIIIA garden bed. The height increment is more optimal in the area with high light intensity (XIV A bed garden) and the diameter increment is more optimal in low light intensity area (XVIIIA bed garden). The increment of height is more influentially to create volume increment. The model showed that height and volume increment have higher R2adjusted value than diameter and volume (0.645 and 0.132, respectively).Key words: Dysoxylum parasiticum (Osbeck) Kosterm., mean annual increment, â€œEka Karyaâ€- Bali Botanical Garden.